The future of molecular chaperones and beyond - Giffard, Rona G.; Macario, Alberto J.L.; Conway de Macario, Everly (The Journal of Clinical Investigation, 2013)
Protection of hair cells by HSP70 released by supporting cells is reported by May et al. in this issue of the JCI. Their findings suggest a new way to reduce ototoxicity from therapeutic medications and raise larger questions about the role and integration of heat shock proteins in non–cell-autonomous responses to stress. Increasing evidence suggests an important role for extracellular heat shock proteins in both the nervous system and the immune system. The work also suggests that defective chaperones could cause ear disease and supports the potential use of chaperone therapeutics.